State Collapse: Government Failure in Gaddafi's Libya - Hariyanti, Carelia Pradita Putri; Porawouw, Fernando Deksi; Nabila, Siti Mufidah Ainun (POPULIKA, 2024)
This article discusses the background and conditions of Libya before and during the reign of Muammar al-Gaddafi, which ended with the fall of his regime in 2011. Libya has a strong economy thanks to its oil resources, but Gaddafi's rule was characterized by strict control and strong policies of Arab nationalism. This research uses a descriptive qualitative method to explain a particular event experienced by an individual or group. The conflict in Libya was triggered by a separatist movement in Benghazi and widespread protests influenced by the Arab Spring. This conflict is closely related to Gaddafi's authoritarian rule that lasted more than 50 years. After Gaddafi's fall in 2011, Libya entered a period of collapse, instability, and prolonged conflict. Libya's post-Gaddafi instability, political turmoil, and economic hardship require holistic solutions such as improved governance, a cohesive national army, financial opportunities, and living standards to reduce migrant safety risks. This article delves into the history of Libya's conflict, its collapse, government transition, restoration efforts, and potential new issues, aiming to provide a comprehensive analysis. Keywords: Libya; Gaddafi; Collapse; Transition; Conflict